A look at the normal development of pointing and reaching gestures and their relationship in 12-16-month-old children speaking Farsi: A longitudinal study - Babaei, Zahra; Zarifian, Talieh; Ashtari, Atieh; Bakhshi, Enayatollah; Ebrahimipour, Mona (Iranian Journal of Child Neurology, 2018)
Objective Human beings can use gestures such as pointing and reaching to communicate with others before they have the ability to use verbal communication to produce speech. Given the importance of children’s communication development and the key role of gestures development in communicating, the main purpose of this study is to analyze the normal development of pointing and reaching gestures and their relationship in 12-16-month-old children speaking Farsi. Methods and materials In this prospective, observational and longitudinal study the gestures of 11 monolingual Farsi- speaking children (7 boys and 4 girls) were evaluated via non-randomized sampling method. Child-mother interactions were videotaped monthly in a semi-structured context to capture the emergence and consistent use of targeted gestures. Afterwards, the data was coded and statistically analyzed for this purpose Repetitive measured, independent T-Test and Pearson correlation were used. Results The mean of the pointing gesture increased significantly from 12 to 16 months (p<0.05). However, this was not significant for the reaching gesture (p>0.05). Moreover, there was no relationship between pointing and reaching gestures (p>0.05). Conclusion The findings of this study suggest that pointing gestures increase with age from 12-16 months in Farsi-speaking children. However, reaching gestures stay the same between 12-16 months of age. The Results are compatible with the other surveys in this area. The study provided rich details of common gestures that children use to signal their intentions before verbal communication.